Elektisisme dalam Bermadzhab Perspektif Fiqh Islam - Samsul Arifin; Suaidi (Al-Adillah: Jurnal Hukum Islam, 2022)
Al-Quran and Al-Hadith are the main sources of footing for Muslims, as well as guide for mankind. Every problem that befell the ummah, they refer directly to this main source. However, not all problems that occur are contained in the source because the text contained in it is universal, so it is really necessary for legal efforts to narrow and clarify the universality of a text. Ideally, this reality requires an intermediary who has the ability to understand the content of the sacred text to respond to all the problems of the people. Without it, the sacred text would be impossible to build into living and sustainable ideas in a Muslim reality. Thus, text processors (mujtahid) are required to be able to dialogue between text and context so that they are able to respond to the dynamics of people's problems. One of the products of ijtihad which until now has become the topic of discussion among scholars is the conception of talfiq in madzhab. This concept is mentioned a lot in various books. One and ushul fiqh. One aspect is considered as a space for freedom for the people in choosing mujtahid opinions and the existence of talfiq as an effort to release the bondage of fanaticism based on madhhab. However, in another aspect, people misunderstand the concept of talfiq, so that in choosing opinions they tend to use opinions that are considered easier for themselves.